Voter Education and Constitutional Democracy: A Socio-Legal Analysis of the Cirebon Regency General Election Commission - Esya Karnia Puspawati; Dewi Sulistianingsih; Martitah; Sunoto (International Journal of Education and Humanities, 2026)
Voter political education constitutes a crucial challenge in consolidating constitutional democracy, particularly in addressing low political awareness, procedural participation, and limited understanding of constitutional values among voters. In many regions, voter participation tends to be driven by administrative compliance rather than informed and responsible civic engagement, which may weaken the substantive quality of democracy. Responding to this problem, this study aims to analyze the role of the General Election Commission in implementing voter political education and to examine its contribution to strengthening constitutional democracy, with specific attention to the practices of the Cirebon Regency General Election Commission. This research employs a socio-legal approach that integrates normative legal analysis and empirical qualitative methods. Normatively, the study examines constitutional provisions, election laws, and regulatory frameworks governing political education for voters. Empirically, qualitative data are derived from official documents, institutional reports, and records of political education activities conducted by the Cirebon Regency General Election Commission. Data are analyzed to assess the alignment between legal mandates and practical implementation at the regional level. The findings indicate that voter political education possesses a strong constitutional and statutory foundation, which legitimizes its implementation as an integral function of election management bodies. In practice, the Cirebon Regency General Election Commission implements political education through educational outreach, inter-institutional collaboration, and adaptive strategies targeting diverse voter groups, particularly first-time voters. These initiatives extend beyond technical election socialization by emphasizing constitutional values, democratic rights, and civic responsibility. The study implies that effective voter political education serves as a strategic bridge between legal norms and democratic practice. Strengthening such programs can enhance constitutional awareness, promote meaningful political participation, and reinforce constitutional democracy at the local and regional levels